Role of Dynamic Capability and Customer Relationship Management: a Case Study of Fintech Lending Platforms in Indonesia - Fortune Nabhel harmony; Soebowo Musa (ADI Publisher, 2020)
The key point for this study is to understand the role of dynamic capability in managing customer relationships for improved business performance. Of utmost interest to this research, the study proposes and tests a model that assumes that dynamic capability has a positive relationship towards customer relationship management; in order to develop organizational agility which has a positive relationship towards firm performance. Upon confirming our hypotheses, our findings offer a clearer picture of the aspects to which the sustainability of a customer relationship management system depends on different organizational capabilities. Hence, dynamic capability can be seen as a catalyst for customer relationship management and business management overall. CRM helps develop agility within an organization and agility strengthens an organization to adapt quickly to its customers ' needs, optimize the operational processes of the organization and establish external relations which influences the firm’s performance.